(untitled) (REMUNOM, 2026)
Nursing education requires preparation for complex environments where decision-making is crucial. Active methodologies such as Team-Based Learning (TBL) have gained prominence by promoting engagement and practical application. This work reports the experience of using TBL with the Raspadinha Pedagógica (Scratch Card teaching tool) and the playful "Saboteur" element for content review. The activity was developed with 21 nursing technician students prior to their internship. Students individually completed a multiple-choice questionnaire with an adaptive scoring system, then reviewed the same questions in teams using the scratch card as an answer key. One team member acted as the Saboteur, introducing conceptual errors. Groups that identified the interference had richer discussions, while others accepted incorrect information. Collective performance surpassed individual performance by 21%. Students reported increased appreciation for knowledge exchange and a heightened awareness of how convictions can be challenged.